Effect of airflow rate on CO2 concentration in downflow indoor ventilation - Guru Sreevanshu Yerragolam; Christopher J. Howland; Rui Yang; Richard J.A.M. Stevens; Roberto Verzicco; Detlef Lohse (Indoor Environments)
We perform direct numerical simulations to study the effect of increasing airflow rate on CO2 concentration in downflow and displacement ventilation in a room with one occupant. Often, CO2 concentration is used as a proxy for the concentration of bio-aerosols of respiratory droplets, and therefore, tracking the CO2 concentration in ventilation strategies can be useful to understand and quantify the risk of spread of communicable respiratory illnesses. At low to moderate airflow rates, the flow in the downflow setup is not mixed, but stratified. The CO2 concentration in the upper and lower layers is determined by the strength of the thermal plume originating from the occupant. We provide a simple theoretical model to predict the height of the stratified interface, the volumetric flux of the ascending plume, and the CO2 concentration in the lower and upper layers. At very high airflow rates, the flow is well-mixed and the average CO2 concentration in the room can be predicted with the mixing ventilation assumption. We demonstrate that at low to moderate airflow rates, displacement ventilation more effectively maintains lower CO2 concentrations in the lower layer compared to downflow ventilation.